Designer Natriuretic Peptides - Lee, Candace Y. W. (2009)
Designer natriuretic peptides (NPs) are novel hybrid peptides that are engineered from the native NPs through addition, deletion, or substitution of amino acid(s) with a goal toward optimization of pharmacological actions while minimizing undesirable effects. In this article, selected peptides that were designed in our laboratory are reviewed, and future directions for research and development of designer NPs are discussed.